1993
DOI: 10.1017/s002211209300391x
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady confined buoyant plumes

Abstract: Two-dimensional time-dependent buoyancy-induced flows above a horizontal line heat source inside rectangular vessels, with adiabatic sidewalls and top and bottom walls maintained at uniform temperature, are studied numerically. Transitions to unsteady flows are performed by direct simulations for various depths of immersion of the source in the central vertical plane of air-filled vessels. For a square vessel and a line source near the bottom wall, the numerical solutions exhibit a sequence of instabilities, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
38
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 27 publications
8
38
0
Order By: Relevance
“…These mechanisms depend on the ratio of depth of immersion to vessel width. The oscillation frequency f = 0.0657Ra 0.433 (0.310 6 < Ra < 810 6 ) [28] as per earlier results [27]. For a pair of cylinders, Eckert and Soehngen [29] found that the induced temperature and velocity fields due to the buoyant plume from downstream cylinders have opposing effects.…”
Section: Case I: Forced Convection Heat Transfer To An Impinging Syntsupporting
confidence: 78%
See 1 more Smart Citation
“…These mechanisms depend on the ratio of depth of immersion to vessel width. The oscillation frequency f = 0.0657Ra 0.433 (0.310 6 < Ra < 810 6 ) [28] as per earlier results [27]. For a pair of cylinders, Eckert and Soehngen [29] found that the induced temperature and velocity fields due to the buoyant plume from downstream cylinders have opposing effects.…”
Section: Case I: Forced Convection Heat Transfer To An Impinging Syntsupporting
confidence: 78%
“…A greater body of research is available on swaying plumes from thin horizontal wires, regarded as line heat sources [25,26,27]. Desrayaud and Lauriat [28] investigated buoyancy induced flow from a horizontal wire heat source; for rectangular vessels two destabilizing mechanisms lead to low frequency motion due to instability of the buoyant plume. These mechanisms depend on the ratio of depth of immersion to vessel width.…”
Section: Case I: Forced Convection Heat Transfer To An Impinging Syntmentioning
confidence: 99%
“…Numerical simulation has been applied to this kind of flows and results with a 2D Direct Numerical Simulation (DNS) have been reported in [5] and [6]. For the validation of our results we are comparing them with those reported in the cited bibliography.…”
Section: Introductionmentioning
confidence: 92%
“…The side walls and the upper wall are maintained at a cold temperature T c , while the remaining walls are kept adiabatic. In addition, in order to deepen our knowledge about natural convection, a special attention will be considered to investigate the phenomena of the unsteady state [4,5].…”
Section: Introductionmentioning
confidence: 99%